Planting the seeds of innovation: Established companies' startup cooperation capability, its mechanisms, and innovation outcomes - Nele Richter; Nicolas A. Zacharias (R&D Management, 2024)
The phenomenon of established companies engaging in startup cooperation in expectance of improving their innovativeness has increased extensively within the last few years. While some companies benefit considerably, others seem to fail at startup cooperation. Bridging cooperation research and dynamic capabilities, this paper sheds light on established companies' startup cooperation capability as important dynamic capability to succeed at startup cooperation. We conceptualize startup cooperation capability adapting alliance capability approaches from traditional cooperation research to fit startup cooperation. Furthermore, this study examines how startup cooperation capability impacts established companies' success in finding potential new startup partners and the efficiency with which startup cooperation activities are coordinated. Through these mechanisms, the study analyzes how startup cooperation capability consequently improves new product innovativeness. In addition, we investigate the moderating effects of resource availability as well as company formalization. To test the hypotheses, we analyze survey data from 195 startup cooperation managers who work at established companies by applying covariance-based structural equation modeling. The results suggest that startup cooperation capability has a positive impact on outreach success, which in turn positively affects new product innovativeness. The relationship between startup cooperation capability and outreach success is strengthened by resource availability. In contrast, startup cooperation capability is negatively associated with coordination efficiency, and this effect is weakened by the influence of company formalization. Summed up, the study shows that startup cooperation capability can improve the innovation outcomes of startup cooperation and illustrates how it can help established companies to pursue startup cooperation successfully.
Keywords: 650